The climatic drivers of primary Picea forest growth along the Carpathian arc are changing under rising temperatures - Schurman, Jonathan S; Babst, Flurin; Björklund, Jesper; Rydval, Miloš; Bače, Radek; Čada, Vojtěch; Janda, Pavel; Mikolas, Martin; Saulnier, Mélanie; Trotsiuk, Volodymyr; Svoboda, Miroslav (Global change biology, 2019)
Climatic constraints on tree growth mediate an important link between terrestrial and atmospheric carbon pools. Tree rings provide valuable information on climate-driven growth patterns, but existing data tend to be biased toward older trees on climatically extreme sites. Understanding climate change responses of biogeographic regions requires data that integrate spatial variability in growing conditions and forest structure. We analyzed both temporal (c. 1901-2010) and spatial variation in radial growth patterns in 9,876 trees from fragments of primary Picea abies forests spanning the latitudinal and altitudinal extent of the Carpathian arc. Growth was positively correlated with summer temperatures and spring moisture availability throughout the entire region. However, important seasonal variation in climate responses occurred along geospatial gradients. At northern sites, winter precipitation and October temperatures of the year preceding ring formation were positively correlated with ring width. In contrast, trees at the southern extent of the Carpathians responded negatively to warm and dry conditions in autumn of the year preceding ring formation. An assessment of regional synchronization in radial growth variability showed temporal fluctuations throughout the 20th century linked to the onset of moisture limitation in southern landscapes. Since the beginning of the study period, differences between high and low elevations in the temperature sensitivity of tree growth generally declined, while moisture sensitivity increased at lower elevations. Growth trend analyses demonstrated changes in absolute tree growth rates linked to climatic change, with basal area increments in northern landscapes and lower altitudes responding positively to recent warming. Tree growth has predominantly increased with rising temperatures in the Carpathians, accompanied by early indicators that portions of the mountain range are transitioning from temperature to moisture limitation. Continued warming will alleviate large-scale temperature constraints on tree growth, giving increasing weight to local drivers that are more challenging to predict.
Keywords: Picea abies; lesy; klimatické změny; growth trends; teplota; synchrony; montane temperate forest; Picea; climate change; smrk; Climate Change; Carpathian arc; Pinus; borovice; Temperature; climate sensitivity; Forests; primary forest